The Esterification of Naphthenic Acids for Methyl Ester Production - Dastjerdi, Zahra (University of Ottawa (Canada), 2010)
The remediation of tailings water, a by-product of bitumen extraction, is of utmost importance to the Athabasca oil sands industry due to its toxicity to aquatic environments. Naphthenic acids (NAs), natural components of bitumen, are the major contributor to the toxicity of tailings water. The use of algae for remediation of tailings water is a new approach to reduce the toxicity of tailings water. The combined extracted NAs and algal oils can potentially be used as a low cost feedstock for the production of biodiesel. In this study, the feasibility of using NAs for the production of biodiesel was investigated using mixtures of canola oil and commercial NAs as model compounds. Since NAs are a mixture of cyclic and acyclic carboxylic acids, the acid-catalyzed esterification of NAs without canola oil was investigated. The acid-catalyzed esterification reaction was carried out with methanol, and the influence of variables affecting the esterification process was examined. The experimental results showed that increasing temperature and catalyst concentration increased the reaction rate and final conversion of NAs to their corresponding methyl esters. The catalyst study showed that sulfuric acid had a more positive effect on the esterification reaction compared to p-toluene sulfonic acid. Additionally, an excess methanol:oil ratio had a negative effect on the esterification reaction due to the solubility of NAs in methanol. The acid-catalyzed transesterification/esterification of mixtures of NA and vegetable oil (canola oil along with 5% NAs) with methanol was investigated at different operating conditions. The outcomes of these experiments showed that increasing temperature, sulfuric acid concentration, and methanol content had positive effects on the rate of reaction and final ester products. The general conclusion of the thesis is that the conversion of NAs to useful products is indeed feasible and can be part of the solution to tar sands tailing pond remediation.
Keywords: Engineering, Chemical.